5th World Congress of Music Therapy, Genoa 1985: An interview with Giovanna Mutti Calcinai - Wheeler, Barbara (Voices: A World Forum for Music Therapy, 2010)
Material on the 5th World Congress of Music Therapy, chaired by Giovanna Mutti and held in Genoa, Italy, in 1985. In addition to its value as an opportunity for people from various countries to share their music therapy work, this congress was important because it is where the World Federation of Music Therapy (WFMT) was established. From this congress to the present, therefore, the world congresses and the WFMT move forward together.